Adult-onset Still's disease with prominent polyserositis. Issue 2 (May 2018) - Farooq Sheikh, Ali Sibtain; Marks, Jonathan; Hopkinson, Neil
Adult-onset Still's disease is a systemic autoinflammatory disease the presentation of which can often mimic infection. As a consequence, there is often a delay in diagnosis. Serositis is a recognised but less common clinical feature that can result in complications including cardiac tamponade and constrictive pericarditis. We describe a case of adult-onset Still's disease without the hallmark rash or significant arthritis, presenting with polyserositis that showed a good response to initial steroid treatment and sustained remission with anakinra. An elevated procalcitonin level was due to active adult-onset Still's disease, not bacterial infection.